Optimasi Keuntungan Penjualan Produk pada Warung Bakso Menggunakan Metode Linear Programming - Amanda Aulia Putri; Dila Adelia; Kelvin Adriano Aditya; Ismar Hidayat (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Increasing competition in the culinary business sector requires entrepreneurs to manage resources efficiently in order to maximize profits. One approach that can be used to determine the optimal production combination is the Linear Programming method. This study aims to optimize product sales profits at Warung Bakso Mas Manda Medan by considering the limitations of available raw materials. The method used in this research is the Simplex Method in Linear Programming. The research data consist of simulated data developed based on the operational conditions of the meatball business, including raw material requirements, production capacity, and profit per product. The results show that the optimal production combination is achieved by producing 80 portions of Bakso Urat and 40 portions of Mie Bakso per day. This combination generates a maximum profit of IDR 1,520,000 per day. The findings demonstrate that the Linear Programming method can assist culinary MSME owners in making more effective and efficient production decisions, thereby increasing business profitability.